A multi-level programming for shale gas-water supply chains accounting for tradeoffs between economic and environmental concerns. (6th April 2020) - Chen, Yizhong; Cheng, Xi; Li, Jing; He, Li
Highlights: A multi-level model is developed for optimal design of the shale gas-water supply chains. Economic and environmental performances of the supply chains are presented. A comprehensive comparison among the single- and multi-level models is discussed. The Marcellus shale is used to verify the application of the multi-level model. Design and operational decisions can be provided for multiple decision makers. Abstract: This study develops a multi-level programming model for planning the shale gas-water supply chains. A set of leader-follower-interactive objectives with emphases of water consumption, economic performance, and pollutant discharge are integrated into a sequential decision-making process. Satisfactory degree is introduced to tackle the computationally challenging problem based on an interactive fuzzy approach. Operational decisions regarding water resources allocation, transportation mode selection, and pollutant discharge control would be achieved. Results reveal that the environmentally- or economically-aggressive strategies would be generated when a single goal for optimizing economic benefits or pollutant discharge. The multi-objective decisions are limited by the selected weights. However, the multi-level model would provide more comprehensive schemes due to its sequential consideration of the economic/environmental concerns. Findings from the multi-level model can facilitate (a) balancing the conflicts among different decision makers, (b) timing and siting for shale gas production, and (c) managing water resources for pollutant discharge control.